2012
DOI: 10.1007/s10974-012-9300-2
|View full text |Cite
|
Sign up to set email alerts
|

What do we know about what happens to myometrial function as women age?

Abstract: Much has been written about the effects of aging on reproductive function, especially female fertility. Much less is known about how aging may affect the contractility of the smooth muscle within the uterus, the myometrium. The myometrium is active through a woman’s entire life, not just during pregnancy. Here we will discuss briefly the contractile functions of the uterus and the changes it undergoes throughout the stages of a woman’s life from menstruation and the menopause, before evaluating the evidence fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
52
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 58 publications
(70 reference statements)
7
52
0
2
Order By: Relevance
“…5,9 The results presented here are broadly in agreement with those reported by Arrowsmith et al 9 in the age range of 25 to 40 years for pregnant myometrium, albeit a more extensive series of experiments are included in the present study. Arrowsmith et al 9 demonstrated that aging decreased uterine contractility in the nonpregnant state but not in tissue obtained in pregnancy.…”
Section: Commentsupporting
confidence: 92%
“…5,9 The results presented here are broadly in agreement with those reported by Arrowsmith et al 9 in the age range of 25 to 40 years for pregnant myometrium, albeit a more extensive series of experiments are included in the present study. Arrowsmith et al 9 demonstrated that aging decreased uterine contractility in the nonpregnant state but not in tissue obtained in pregnancy.…”
Section: Commentsupporting
confidence: 92%
“…In vitro investigations of myometrical strips among pregnant and non-pregnant women with increasing age have shown a decreased contractility with increasing age, although it was not statistically significant among pregnant women 115 . Hence, in theory, the effect of oxytocin augmentation with increasing age could reduce the risk of prolonged labor and cesarean section among these women, but further investigation is needed 116,117 .…”
Section: Maternal Age and The Role Of Oxytocinmentioning
confidence: 88%
“…25 Similarly, myometrial tissue high in cholesterol has been reported to have decreased contractility in comparison to tissue with a low cholesterol content. 41 In nonmyometrial cell culture, modulation of cholesterol within the cell membrane has been shown to affect the cellular response to oxytocin stimulation: in the presence of cholesterol, oxytocin receptors localize to lipid rafts and cellular proliferation was noted, but after cholesterol depletion, these receptors localized away from lipid rafts and inhibition of cell growth was demonstrated. 38 Although these experiments suggest that cholesterol has the potential to affect myometrial contractility and function, data are currently lacking to link these in vitro observations to specific clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%